Isogambogenic Acid Inhibits the Growth of Glioma Through Activation of the AMPK-mTOR Pathway - Wenyang Zhao (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Glioma is the most devastating cancer in the brain and has a poor prognosis in adults. Therefore, there is a critical need for novel therapeutic strategies for the management of glioma patients. Isogambogenic acid, an active compound extracted from the Chinese herb Garcinia hanburyi, induces autophagic cell death. Methods: Cell viability was detected with MTT assays. Cell proliferation was assessed using the colony formation assay. Morphological changes associated with autophagy and apoptosis were tested by TEM and Hoechst staining, respectively. The apoptosis rate was measured by flow cytometry. Western blot, immunofluorescence and immunohistochemical analyses were used to detect protein expression. U87-derived xenografts were established for the examination of the effect of isogambogenic acid on glioma growth in vivo. Results: Isogambogenic acid induced autophagic death in U87 and U251 cells, and blocking late-stage autophagy markedly enhanced the antiproliferative activities of isogambogenic acid. Moreover, we observed the activation of AMPK-mTOR signalling in isogambogenic acid-treated glioma cells. Furthermore, the activation of AMPK or the inhibition of mTOR augmented isogambogenic acid-induced autophagy. Inhibition of autophagy attenuated apoptosis in isogambogenic acid-treated glioma cells. Finally, isogambogenic acid inhibited the growth of U87 glioma in vivo. Conclusion: Isogambogenic acid inhibits the growth of glioma via activation of the AMPK-mTOR signalling pathway, which may provide evidence for future clinical applications in glioma therapy.